Sediment-filled karst depressions and riyad: key archaeological environments of south Qatar - Engel, Max; Rückmann, Stefanie; Drechsler, Philipp; Brill, Dominik; Opitz, Stephan; Faßbinder, Jörg W. E.; Pint, Anna; Peis, Kim; Wolf, Dennis; Gerber, J. Christoph; Pfeiffer, Kristina; Eichmann, Ricardo; et al. (Quaternary science journal, 2020)
Systematic archaeological exploration of southern Qatar started in the 1950s. However, detailed local and regional data on climatic fluctuations and landscape changes during the Holocene, pivotal for understanding and reconstructing human-environment interactions, are still lacking. This contribution provides an overview on the variability of geomorphic environments of southern Qatar with a focus on depression landforms, which reveal a rich archaeological heritage ranging from Palaeolithic(?) and Early Neolithic times to the Modern era. Based on a detailed geomorphic mapping campaign, sediment cores and optically stimulated luminescence data, the dynamics of riyad (singular rawdha; shallow, small-scale, sediment-filled karst depressions clustering in the central southern peninsula) and the larger-scale Asaila depression near the western coast are studied in order to put archaeological discoveries into a wider environmental context. Geomorphic mapping of the Asaila basin shows a much greater geomorphic variability than documented in literature so far with relict signs of surface runoff. An 8 m long sediment core taken in the sabkha-type sand flats of the western basin reveals a continuous dominance of aeolian morphodynamics during the early to mid-Holocene. Mounds preserved by evaporite horizons representing capillarites originally grown in the vadose zone are a clear sign of groundwater-level drop after the sea-level highstand ca. 6000-4500 years ago. Deflation followed the lowering of the Stokes surface, leaving mounds where the relict capillarites were able to fixate and preserve the palaeo-surface. Abundant archaeological evidence of Early and Middle Neolithic occupation - the latter with a clear focus inside the central Asaila basin - indicate more favourable living conditions than today. In contrast, the sediment record of the investigated riyad in the south is very shallow, younger and controlled by surface discharge, deflation and the constantly diminishing barchan dune cover in Qatar over the Middle and Late Holocene. The young age of the infill (ca. 1500 to 2000 years) explains the absence of findings older than the Late Islamic period. Indicators of current net deflation may relate to a decrease in surface runoff and sediment supply only in recent decades to centuries. In the future, geophysical prospection of the riyad may help to locate thicker sedimentary archives and the analysis of grain size distribution, micromorphology, phytoliths or even pollen spectra may enhance our understanding of the interplay of regional environmental changes and cultural history.
Gesehen am 20.05.2021